Uso de drogas entre adolescentes em situação de rua no município de São Paulo: uma contribuição etnográfica - Moura, Yone Gonçalves de [UNIFESP] (2006)
INTRODUCTION: Numerous studies have shown that drug intake is a common behavior among adolescents living in the streets, being associated to many health risks. In Brazil, despite the many epidemiologic surveys about this situation, qualitative assessments are still lacking. OBJECTIVE: To understand the use of drugs among adolescents living in the streets of São Paulo City, by means of two ethnographic techniques: observational evaluation of and semi-structure interviews with adolescents living in the streets. METHODS: Observational assessments were performed in specialized institutes and at places of higher concentration of adolescents (points), at different periods of the day. The observations were recorded in field diaries for subsequent analysis. Seventeen adolescents, aged 12 to 18 years were interviewed by direct approach at the streets or at the institutions, by the “snow ball” technique. The interviews followed a semi-structure script with the focus on the interviewee’s perception and his/her life in the following aspects: personal information, family/school history, social network, life expectancies and, in respect to the drugs, social context and pattern of use, the function of drugs on the adolescents’ life, availability of the drugs, onset of use and beliefs. The interviews were anonymous, recorded with the participant’s previous consent, subsequently transcribed and coded for content analysis. RESULTS AND DISCUSSION: The observation of the participant revealed that several social factors influence the daily dynamics of the adolescents and their drug use behavior. Among these factors, group features, activities performed, the street movement, police movement and traffic can be included, The choices made by the adolescents also appeared to be under the influence of inner factors, such as curiosity, pleasure seeking and self-esteem. The field observations, enriched by the testimonies of the interviewees, showed associations between the pattern of drug use and the adolescent’s life style, which were grouped in three categories. One of them was characterized by high intensity drug use and insertion in the street cultural style; the second category was represented by a lesser use and more proximity to the family; and in the third category, there was a greater involvement with traffic, prostitution and less closeness to the street culture. Nonetheless, we observed some more general data, such as the trajectory of the use, which varied among the interviewees as a consequence of their personal history. Several risk behaviors associated to the drug 80 seeking and to the level of intoxication were also reported. The drug was seen as an important factor of social integration to the adolescent, working as a mediator of the process. The study showed the importance of the social networks, especially the street “brothers”, the specific institutions for people living in the streets, health services, family, school, police, commerce and traffic. These systems show assemblies that varied according to each particular street situation. Based on these results, it is possible to conclude that thinking of drug use behavior without considering it within a socio-cultural context, implies in ignoring its complexity and, therefore, impoverishing the possibilities of social interventions.